LOW SPEED IMPACT PERFORMANCE AND APPLICATION OF FLAX-BASALT FIBER COMPOSITES (MT) - ZHANG RuHao; CUI An; CHEN Chong; YU TianMing; LIU LiYuan; HUANG XianQing (Jixie qiangdu)
In order to meet the requirements of vehicle lightweight and crash safety, flax-basalt fiber composite laminates were made. The tensile, shear and impact resistance properties of the composite structure were discussed through test and simulation analysis. Using the three-dimensional Hashin failure criterion of strain form and the stiffness linear degradation scheme based on fracture toughness, the Vumat subroutine was compiled to establish a low-speed impact finite element model. The effects of ply structure and ply angle on the low-speed impact resistance of laminates were studied. The flax-basalt fiber laminate structure was applied to the inner and outer panels of engine hood under static conditions and children’s head impact simulation analysis. The results show that the static stiffness and weight reduction effect of the structure are better than steel engine cover, the child head protection performance meets the requirements, and the performance improvement is more obvious when the inner plate adopts the composite structure.